Synthesis and Characterization of Nickel Nanoparticles: Biological and Photocatalytic Properties - Fadliah, Fadliah; Raya, Indah; Ahmad, Ahyar; Taba, Paulina; Burhanuddinnur, Muhammad; Gaffar, Maming; Putri, Tri Widayati; Nur, Arfiani; Abubakar, Andi Nur Fitriani; Munadi, Rachmin; Majid, Ahmad Fudhail; Pratama, Irham; Yasser, M.; Jarre, Sulistiani; Karim, Harningsih (Indonesian Journal of Chemistry, 2025)
The potential uses of ecologically benign nickel nanoparticle manufacturing in various sectors, such as biomedicine, energy storage, and catalysis, have garnered much interest. This paper covers green approaches to nickel nanoparticle manufacturing, which integrate natural substances as stabilizing and reducing agents with eco-friendly processes. Phytochemicals derived from bacteria, microorganisms, and plant leaf extracts can convert nickel ions (Ni2+) into nickel nanoparticles. Room temperature is used for the synthesis procedure, and neither dangerous compounds nor unusual reaction conditions are used. Using a variety of analytical methods, the resultant nickel nanoparticles were characterized. We also investigate the possibility of using the generated nickel nanoparticles as a cytotoxic, photocatalytic, antioxidant, and antibacterial agents. The antimicrobial activity of nickel nanoparticles demonstrates their potent antibacterial properties, while their antioxidant activity demonstrates their capacity to combat free radicals effectively. Furthermore, nickel nanoparticles' cytotoxic activity demonstrates their capacity to kill cancer cells, and their photocatalytic activity demonstrates their efficiency in breaking down organic contaminants. This review highlights the value of ecologically benign synthetic methods and creates new avenues for developing nickel nanoparticle applications in health and the environment.